Simulasi Sistem Keamanan Palang Pintu Perlintasan Kereta Api Menggunakan LabVIEW - Sarnia Rizki Oktareza; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Infrared sensor and photodiode is widely used in a wide variety of applications, ranging from the military field, health and so forth. Infrared sensor and photodiode can detect any objects that pass nearby, it is because the infrared sensor and photodiode has a high sensitivity. The railway gate security system, infrared sensor very helpful. The secutiry systems designed using LabVIEW can work by monitoring sensors connected to the microcontroller Arduino Uno. The program on Arduino microcontroller designed by entering commands to be execute. To run the simulations, LabVIEW and Arduino should be interfaced first in order to communicate well. NI-VISA application is added as a means between LabVIEW and Arduino in LabVIEW.Keywords : Infrared, Photodiode, Arduino, LabVIEW, Microcontroller, Interface